AMMO-Prot: Amine system project 3D-model finder - Navas-Delgado, Ismael; Pino-Ángeles, Almudena; Montañez, Raúl; Moya-García, Aurelio Ángel; Urdiales-Ruiz, José Luis; Sánchez-Jiménez, Francisca María; Aldana-Montes, José Francisco (Springer Nature, 2008)
Background: Amines are biogenic amino acid derivatives, which play pleiotropic and very important yet complex roles in animal physiology. For many other relevant biomolecules, biochemical and molecular data are being accumulated, which need to be integrated in order to be effective in the advance of biological knowledge in the field. For this purpose, a multidisciplinary group has started an ontology-based system named the Amine System Project (ASP) for which amine-related information is the validation bench. Results: In this paper, we describe the Ontology-Based Mediator developed in the Amine System Project (http://asp.uma.es) using the infrastructure of Semantic Directories, and how this system has been used to solve a case related to amine metabolism-related protein structures. Conclusions: This infrastructure is used to publish and manage not only ontologies and their relationships, but also metadata relating to the resources committed with the ontologies. The system developed is available at http://asp.uma.es/WebMediator.
Keywords: Aminas; Semantic Ontology; Protein modeling; Systems Biology